Evaluation of the anti-RANKL monoclonal antibody in rheumatoid arthritis rats - Dawei Lv,; Xiaodong Zhao, (Archives of Rheumatology, 2023)
Objectives: In this study, we aimed to investigate the therapeutic effect of anti-receptor activator of nuclear factor kappa-κB ligand (RANKL) monoclonal antibodies R748-1-1-1, R748-1-1-2 and R748-1-1-3 on rheumatoid arthritis (RA) in a rat model. Materials and methods: Gene cloning, hybridoma technology, affinity purification, enzyme-linked immunosorbent assay, general observation, hematoxylin-eosin staining, X-ray, and many other experimental techniques were used in this study. Results: Improved collagen-induced arthritis (CIA) modeling was successfully constructed. The RANKL gene was cloned and the anti-RANKL monoclonal antibody was prepared. Following treatment with the anti-RANKL monoclonal antibody, the soft tissue swelling of the hind paws, the joint thickening, the narrowed joint gap, and the blurred edge of the bone joint were improved. The pathological changes such as synovial hyperplasia of fibrous tissue, cartilage and bone destruction were significantly decreased in the anti-RANKL monoclonal antibody-treated CIA group. Compared to the normal control group and phosphate buffer saline (PBS)-treated CIA group, the expression of tumor necrosis factor-alpha (TNF-α) and interleukin-1 (IL-1) in antibody-treated CIA group, positive drug-treated CIA group, and IgG-treated CIA group were decreased (p<0.05). Conclusion: The anti-RANKL monoclonal antibody can promote the therapeutic effect of RA rats, indicating that the anti-RANKL monoclonal antibody has a certain potential value and may be beneficial to the further study of the mechanism of RA treatment.